1984
DOI: 10.1111/j.1469-8137.1984.tb02742.x
|View full text |Cite
|
Sign up to set email alerts
|

New Nodulating Legume Trees From South‐east Brazil

Abstract: SUMMARYAn extensive search for active (acetylene reducing) nitrogen-fixing root nodules was made amongst Brazilian forest legumes. Seven new nodulated species, including two new nodulating genera, were found in the Caesalpinioideae, 18 new species in the Mimosoideae and 30 new species, including four new genera, in the Papilionoideae. All have potential importance in reafforestation. Fifty-eight new records of non-nodulating species are included. The morphology of all nodules was studied and is discussed in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(51 citation statements)
references
References 7 publications
5
43
0
3
Order By: Relevance
“…In our study, the low frequency observed (71% of species) is due to the presence of the Parkieae, a tribe known for its absence of nodulation in the type-genus (De Faria et al, 1984 ;Sprent, 1995). Nodulation is known to be variable in the Mimoseae, particularly in the genera Pseudopiptadenia and Stryphnodendron .…”
Section: Nodulation In the Leguminosaementioning
confidence: 50%
See 1 more Smart Citation
“…In our study, the low frequency observed (71% of species) is due to the presence of the Parkieae, a tribe known for its absence of nodulation in the type-genus (De Faria et al, 1984 ;Sprent, 1995). Nodulation is known to be variable in the Mimoseae, particularly in the genera Pseudopiptadenia and Stryphnodendron .…”
Section: Nodulation In the Leguminosaementioning
confidence: 50%
“…Among the Detarieae, nodulation has not been observed in 13 genera including Copaifera, Peltogyne and Crudia (De Faria et al, 1984 ;1987a. The incidence of nodulation in the genus Eperua is uncertain, since it has been reported in only one species of the 14 known (Allen & Allen, 1981).…”
Section: Nodulation In the Leguminosaementioning
confidence: 99%
“…Abundance (count model component) of E. falcata was negatively related to low soil nitrogen values. This species, along with others of the same genus, are generally able to produce nitrogen-fixing root nodules (Faria et al, 1984(Faria et al, , 1989Schimann et al, 2008). However, its roots have a unique strategy to acquire soil nitrogen.…”
Section: Variables Related To Species Occurrence and Abundancementioning
confidence: 99%
“…The roots do not exploit available nitrogen in the soil, and instead use nitrogen in the leaf litter (Chesney and Vasquez, 2007;Payan et al, 2009 on E. poeppigiana in agroforestry systems), an environmental variable that was analysed in our study. Conversely, M. frondosus, another Fabaceae species, was not reported to produce nitrogen-fixing nodules (Allen and Allen, 1981;Faria et al, 1984).…”
Section: Variables Related To Species Occurrence and Abundancementioning
confidence: 99%
“…Vale ressalvar, porém, que apesar de ser uma espécie fixadora de N 2 , a mangium tendeu a retranslocar um percentual significativo de N antes que seus filódios senescessem (Tabela 2) o que corrobora com a mobilidade desse elemento dentro da planta e com a idade do plantio. Em conseqüência da introdução constante de resíduos com relação C/N estreita e ao estoque de matéria orgânica (e N) sobre o solo em áreas de ocorrência de leguminosas, a nodulação passa a ser escassa por parte dessas espécies (Faria et al, 1984). A ciclagem do N existente na área passa a ser suficiente no atendimento da demanda e manutenção destas no ecossistema, além de ser mais econômico fisiologicamente para a espécie adquirir nitrogênio na forma combinada do que em simbiose.…”
Section: Eficiência De Uso E Taxa De Retranslocação De N P K Ca E Mgunclassified